If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 6j = 5p Solving c + 6j = 5p Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6j' to each side of the equation. c + 6j + -6j = -6j + 5p Combine like terms: 6j + -6j = 0 c + 0 = -6j + 5p c = -6j + 5p Simplifying c = -6j + 5p
| 7(x-3)=3(7-2x)+13x | | x^2(a-b)-a(a-b)=0 | | 35=-7(2-x) | | 2x(5)=21 | | uw+uv=r | | 3x^2+10x-11=3-9x | | 6x-3-6x-8=11x | | 10-2(a+2)=9+a | | 45x^2-42x^3-24x^4=0 | | (x+4)+=-21 | | 2t-11=-4t+1 | | 4w-6=14 | | 20x^3+33x^2+7x= | | .20x+.50=1 | | -4(y-4)=-4y+8 | | -7(x-5)+2=37 | | 2n+7n=63 | | 4(2r+1)-3(2r-5)=40 | | 6-6x+8+3x+4x-3=5+3(4) | | 16+3=10x-5 | | 2d+3=4(d-1) | | -10(b-3)=100 | | 0.5+6=36 | | 28x^3-6x^2-4x=0 | | 3/4(z-1/9)=1/9(z-1/8) | | -10x=2+10x-8+1 | | 5x^2-9x-18= | | 8(4)-4(4-2)=24 | | q=4h+4z | | 8+7n=9.5-4n | | -4(m+5)+2m=3(m+2) | | (4-z)(-1)= |